"Listen to the parents… really listen to the child!" Family narratives of supporting children hearing voices. Issue 3 (3rd July 2021) - Parry, Sarah; Varese, Filippo
ABSTRACT: Background Despite the vital role parents play in caring for children with auditory hallucinations, very little research has garnered their experiences, opinions and recommendations for improving service design and delivery. Methods 132 participants ( M age = 39.11; SD = 8.50) from 14 countries completed an online qualitative survey, providing rich reflective narratives about their individual and systemic experiences of caring for a child with auditory hallucinations. Narratives were analyzed through a Foucauldian-informed narrative analysis, which recognized the influence of internalized stigma and societal narratives that surround hallucinations across Western cultures. Results Four emancipatory narratives provide novel insights into the experience of caring for a young voice-hearer. Participants discussed their first thoughts and reactions, which were often influenced by negative societal narratives surrounding voice-hearing and fears for the future, as well as how a lack of tailored systemic support could adversely affect family functioning. Conclusions Parents require greater access to, and inclusion in, intervention pathways within mental health services. Mothers may require additional resource due to a lack of systemic support and risks to their wellbeing as they care for their child. Participants recommend changes for clinical care, including earlier early intervention pathways for young children, easily accessible online information, support groups, and parent training programs.